Pengaruh Gaya Kepemimpinan Transformasional dan Keterlibatan Kerja Terhadap Kinerja Karyawan Pada PT Pegadaian Cabang Malalayang Manado - FY. Rantung, Amanda; Rumawas, Wehelmina; DS Mukuan, Danny (Universitas Sam Ratulangi, 2026)
This study aims to analyze the influence of transformational leadership and work engagement on employee performance at PT Pegadaian Malalayang Branch, Manado. This research uses a quantitative associative approach with a census sampling technique involving 38 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that transformational leadership has a positive and significant effect on employee performance and work engagement. Meanwhile, work engagement shows a positive but not significant effect on employee performance. These findings suggest that transformational leadership plays a dominant role in improving employee performance through inspiration, motivation, and individual consideration. Therefore, organizations are encouraged to strengthen leadership quality as a strategic effort to achieve optimal and sustainable employee performance.